Intra-articular pressure profiles of the cadaveric equine fetlock joint in motion - Macoris, D. D.; Bertone, A. (Equine Veterinary Journal Ltd, 2001)
The study of the influence of motion and initial intra-articular pressure (IAP) on intra-articular pressure profiles in equine cadaver metatarsophalangeal (MTP) joints was undertaken as a prelude to in vivo studies, Eleven equine cadaver MTP joints were submitted to 2 motion frequencies of 5 and 10 cycles/min of flexion and extension, simulating the condition of lower and higher (double) rates of passive motion. These frequencies were applied and pressure profiles generated with initial normal intra-articular pressure (-5 mmHg) and subsequently 30 mmHg intra-articular pressure obtained by injection of previously harvested synovial fluid.The 4 trials performed were 1) normal IAP; 5 cyles/min; 2) normal IAP; 10 cycles/min; 3) IAP at 30 mmHg; 5 cycles/min and 4) IAP at 30 mmHg; 10 cycles/min. The range of joint motion applied (mean +/- s.e.) was 67.6 +/- 1.61 degrees with an excursion from 12.2 +/- 1.2 degrees in extension to 56.2 +/- 2.6 degrees in flexion, Mean pressure recorded in mmHg for the first and last min of each trial, respectively, were 1) -5.7 +/- 0.9 and -6.3 +/- 1.1; 2) -5.3 +/- 1.1 and -6.2 +/- 1.1; 3) 58.8 +/- 8.0 and 42.3 +/- 7.2; 4) 56.6 +/- 3.7 and 40.3 +/- 4.6. Statistical analyses showed a trend for difference between the values for the first and last minute in trial 3 (0.05>P<0.1) with P = 0.1 and significant difference (P = 0.02) between the mean IAP of the first and last min in trial 4. The loss of intra-articular pressure associated with time and motion was 10.5, 16.9, 28.1 and 28.9% for trials 1-4, respectively. As initial intraarticular pressure and motion increased, the percent loss of intra-articular pressure increased.The angle of lowest pressure was 12.2 +/- 1.2 (mean +/- s.e.) in extension in trials 1 and 2, In trials 3 and 4, the lowest pressures were obtained in flexion with the joints at 18.5 +/- 2.0 degrees (mean +/- s.e.). This demonstrated that the joint angle of least pressure changed as the initial intra-articular pressure changed and there would not be a single angle of least pressure for a given joint.The volume of synovial fluid recovered from the MTP joints in trial 3 compared to 4 (trials in which fluid was injected to attain IAP of 30 mmHg) was not significantly different, supporting a soft tissue compliance change as a cause for the significant loss of intra-articular pressure during the 15 min of trial 4.The pressure profiles generated correlate well with in vivo values and demonstrated consistent pressure profiles. Our conclusions are summarised as follows:1. Clinically normal equine MTP joints which were frozen and then later thawed were found to have mostly negative baseline intra-articular pressures, as would be expected in living subjects,2. Alternate pressure profiles of the dorsal and plantar pouch at baseline intra-articular pressure document the presence of pressure forces that would support 'back and forth' fluid movement between joint compartments. This should result in movement of joint fluid during motion, assisting in lubrication and nutrition of articular cartilage,3. If joint pressure was initially greater than normal (30 mmHg), as occurs in diseased equine MTP joints, joint motion further increased joint capsule relaxation (compliance) and, therefore, reduced intra-articular pressure.4. Peak intra-articular pressures reached extremely high values (often >100 mmHg) in flexion when initial pressure was 30 mmHg. Joint effusion pressures recorded for clinical MCP joints are frequently 30 mmHg. These IAP values are expected to produce intermittent synovial ischaemia in clinical cases during joint flexion.5, Additional in vivo studies are necessary to confirm our conclusions from this study and to identify the contributions of fluid absorption and the presence of ischaemia in a vascularised joint.
Keywords: Horse; intra-articular pressure; cadaver; exercise physiology; passive motion; pressure profiles